PROPAGATION OF AVOCADO CV. FUERTE BY HERBACEOUS CUTTINGS - Mindêllo-Neto, Ubirajara Ribeiro; Hirano, Elcio; Telles, Charles Allan; Biasi, Luiz Antonio (Scientia Agraria, 2006)
This work was done with the purpose to evaluate the effect of the indolbutyric acid (IBA) concentration and immersion time for rooting of herbaceous cuttings of avocado cv. Fuerte. The cuttings were treated with IBA at concentrations of 0, 500, 1.000, 2.000 and 4.000 mg.L-1 of IBA in two immersion periods (5 seconds and 24 hours) according to each treatment. All cuttings tested were placed in a substrate with sand medium texture in expanded poliestirene trays with 72 cells. Afterward the treated cuttings were placed inside intermittent mist greenhouse for 185 days. The highest percentage of rooted cuttings (47,5 %) was obtained by immersion for 5 seconds at the concentration of 500 mg.L-1 of IBA. The immersion of cuttings in distilled water promoted the rooting regardless the immersion time. The rooting percentage was zero when the cuttings were immersed into hydro-alcoolic solution of IBA for 24 hours.